Distribution of Dactylis glomerata in rangelands of Takab City (case study: Golun rangelands) - َAmin Mahmoodian Chooplu; Hamid Niknahad (علوم محیطی)
Introduction: Determining the response of plant species to environmental gradients is an important issue in the analyses of vegetation communities. The purpose of the present study was to investigate the most important environmental factors shaping the occurrence of Dactylis glomerata in Takab rangelands. Material and methods: Eighty four plots (1m2) were placed random-systematically along the azimuth of the studied area. In each plot, the presence of the species was recorded and one soil sample at the depth of 0–20 cm was collected. Some soil physical and chemical properties including soil moisture, texture, pH, electrical conductivity, organic carbon percentage, and the percentage of total nitrogen were measured in the laboratory. Data analysis was performed by Rver.3.0.2 statistical software. The binomial distribution of the Huisman – Olff - Fresco (HOF) function was used to fit the curve of species response to environmental gradients. Results and discussion: The results demonstrated that the altitude variable is the most important environmental factor affecting D. glomerata distribution. Moreover, the optimal ecological amount of this variable for D. glomerata is 2100 m above sea level. After altitude, slope (%), soil organic carbon (%), soil total nitrogen (%), and soil moisture content were the most effective factors on the distribution of D. glomerata. Conclusion : In general, D. glomerata was more distributed in the lower slope of mountainous areas with high soil organic matter and moisture content.